Comparação de métodos convencionais e reação em cadeia da polimerase em tempo real na detecção de infecção pelo citomegalovírus in vitro - Cezar, Amanda Cristina [UNIFESP] (2009)
Introduction: Clinical isolates of Cytomegalovirus (CMV) are easily spread in vitro resulting in impairment of the monolayer cell where the virus was inoculated, thus evidencing the presence or absence of infection. The cell culture is a classic method for detection of CMV and it was widely used in the past. Antigenemia assay, which detects CMV pp65 antigen, is the method most used currently in clinical practice, because it is faster and specific for detection of the active infection. Recently, the real-time PCR has been used in monitoring of the infection through the quantification of viral load for being a high sensitivity and specificity method to viral DNA. Therefore, the aim of the study was employing tests used in diagnosis and monitoring of infection to the standard CMV strain as a protocol for implantation in experiments in vitro. Methods: Quiescent human fibroblasts in confluent monolayer were inoculated with samples of infected cells by the adapted CMV AD169 strain. The effect of the virus on culture was monitored at 1 hour, 24 hours, 48 hours and 72 hours post infection (h.p.i) by observation of cytopathic effect. The same samples were analyzed by antigenemia being estimate the mean of positive cells in 2x105 cells and by real-time PCR being estimate the mean of copies of viral DNA/Log10 present in samples. Results: Cytopathic effect was first noticed 24 h.p.i, showing that the initiation of morphological changes occurred early. This effect became more intense after 72 h.p.i. Antigenemia assay showed the presence of active infection through pattern of labeling of the pp65 viral antigen found on nucleus of infected cells, while the real-time PCR showed the number of copies of viral DNA in different times of infection. Antigenemia showed an mean of 57 ±56 positive cells 1h.p.i. The peak of the infection was reached 24h.p.i with a significant increase in the mean 2.381 ±168 (P<0.05 versus 1h.p.i) and remained high 48h.p.i, showing an mean of 2.012 ±352 positive cells. However, the mean of antigenemia decrease 72h.p.i to 262 ±5 (P<0.05 versus 48h.p.i). As well as in antigenemia, a significant increase of th viral load was observed of 1h.p.i to 24h.p.i, being the mean of viral DNA detected 11.30 ±0.30 and 11.96 ±0.09, respectively (P<0.05). The levels of viral DNA stayed high 48h.p.i, being detected a mean of 12.33 ±0.26. After this period, viral load decreased significantly to 11.57 ±0.06 (P<0.05 versus 48h.p.i). No correlation was found between the quantitative methods of antigenemia and real-time PCR. Conclusion: The three methods, virus isolation, antigenemia and real-time PCR, showed the success of the CMV infection “in vitro” by cyto-morphological changes, detection of viral antigen specific and viral load by virus DNA detection, respectively. PCR method was more sensitive in detecting virus in relation the other methods. Although sensitive and specific, we consider the need for viral titration in any experimental studies in vitro.